Gut Microbiota of Chinese Obese Children and Adolescents With and Without Insulin Resistance - Yuan, Xin; Chen, Ruimin; Zhang, Ying; Lin, Xiangquan; Yang, Xiaohong; McCormick, Kenneth L. (Frontiers in Endocrinology, 2021)
Objective The intestinal flora of gut microbiota in obese Chinese children and adolescents with and without insulin resistance (IR) was analyzed, as well as associations between the gut microbiota and serum cytokines, especially those related to glucose metabolism, adropin and angiopoietin-like 4 (ANGPTL4). Methods Clinical data, fecal bacterial composition, glucose-related hormones, and serum adipokines (adropin and ANGPTL4) were analyzed in 65 Chinese children with exogenous obesity. The composition of the gut microbiota was determined by 16S rRNA-based metagenomics and IR was calculated using the homeostasis model assessment (HOMA). Results The 65 obese subjects were divided into two groups: insulin sensitive (IS) (n=40, 57.5% males) or IR (n=25, 60% males). Principal coordinates analysis revealed that the gut microbiota samples from the IS group clustered together and separated partly from the IR group (p=0.008). By Mann-Whitney U-test, at a phylum level, a reduction of Firmicutes and an increase of Bacteroidetes in the IR subjects was observed. LEfSe analysis revealed that IS subject, when compared to their IR counterparts, harbored members of the order Coriobacteriales, Turicibacterales, Pasteurellales and family Turicibacteraceae, that were significantly more abundant. In contract, the IR subjects had members of family Peptococcaceae that were significantly more prevalent than the IS subjects (all p<0.05). Spearman’s correlation analysis revealed that serum ANGPTL4 was positively associated with genus Bacteroides, Butyricimonas and Alistipes, and adropin was positively associated with genus Anaerostipes and Alistipes, and negatively associated with genus Blautia (all p<0.05). Conclusion In obese children, the gut microbiome in IR subjects was significantly discordant from the IS subjects, and the abundance of some metabolism-related bacteria correlated with the serum concentrations of adropin and ANGPTL4. These observations infer that the gut microbiota may be involved in the regulation of glucose metabolism in obesity.